Experimental and numerical investigation into ultimate capacity of longitudinal plate-to-circular hollow section K- and DK-joints in transmission towers. (October 2019) - Li, Fang; Deng, Hong-zhou; Hu, Xiao-yi
Abstract: Longitudinal plate-to-circular hollow section DK-joints are generally used in transmission towers. In this study, the ultimate bearing capacities of planar K- and multiplanar DK-joints were investigated. Full-scale three-dimensional experiments involving DK-joints were performed, and parametric studies were conducted to obtain the ultimate capacities of K- and DK-joints. In the simulation study of K- and DK-joints, branch axial forces were resolved into a bending moment ( M w ) and a vertical component force ( P v ). Ultimate strength equations for M w and P v are proposed and compared with current guidelines. DK-joints have two branch plates, whereas K-joints have only one. Hence, the ultimate capacities of these two joints were compared for a single branch plate. Analysis results showed that in transmission towers, the ultimate capacity of the equivalent bending moment for DK-joints is about 0.89–1.0 times that of the equivalent bending moment for K-joints, and that the ultimate capacity of the vertical component force for DK-joints is about 0.605 times that of the vertical component force for K-joints. Interaction equations for M w and P v are proposed for both joints. Predictions of the proposed equations are in agreement with the existing test results. Highlights: Difference and relationship between plate-to-CHS K- and DK-joints were studied. Full-scale three-dimensional experiments of DK-joints was achieved. Ultimate strength equations for K- and DK-joints were proposed. Failure modes of K- and DK-joints were compared.